Growth and Primary Metabolism of Lettuce Seedlings (Lactuca sativa L.) Are Promoted by an Innovative Iron-Based Fenton-Composted Amendment - Amalia Piro; Daniela Oliva; Dante Matteo Nisticò; Ilaria Lania; Maria Rita Basile; Giuseppe Chidichimo; Silvia Mazzuca (Plants, 2023)
Information regarding the physiological and molecular plant responses to the treatment with new biofertilizers is limited. In this study, a fast-composting soil amendment obtained from solid waste by means of a Fenton reaction was assessed to evaluate the effects on the growth of Lactuca sativa L. var. longifolia seedlings. Growth rate, root biomass, chlorophyll concentration, and total soluble proteins of seedlings treated with the 2% fast-composting soil amendment showed significant increases in comparison with the control seedlings. Proteomic analysis revealed that the soil amendment induced the up-regulation of proteins belonging to photosynthesis machinery, carbohydrate metabolism, and promoted energy metabolism. Root proteomics indicated that the fast-composting soil amendment strongly induced the organs morphogenesis and development; root cap development, lateral root formation, and post-embryonic root morphogenesis were the main biological processes enriched by the treatment. Overall, our data suggest that the addition of the fast-composting soil amendment formulation to the base soils might ameliorate plant growth by inducing carbohydrate primary metabolism and the differentiation of a robust root system.